A Cultivating Grit Through Mindfulness and Self-Compassion Among Indonesian Islamic Primary School Students - Krismona, Elwas Berdha; Andrianie, Santy; Wulandari, Arifah; Bariyyah, Khairul; Abu Bakar, Abu Yazid; Restuningsih, Anastasya (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
Grit is an individual's ability to maintain perseverance and commitment in achieving long-term goals. Low grit among students results in decreased motivation to learn, reduced academic responsibility, and an increased risk of dropping out of school. This study aims to examine the effects of mindfulness and self-compassion on grit among Islamic elementary school students. The study used a quantitative approach with a correlational design. The study subjects consisted of 267 students in grades 4, 5, and 6 from Islamic elementary schools in the provinces of East Java and Central Java. Data were obtained through the distribution of psychological scales adapted from the Child and Adolescent Mindfulness Measure (CAMM), the Self-Compassion Scale Short Form for Children (SCS-SF-C), and the Grit Scale for Elementary School. Data analysis was conducted using multiple linear regression. The results showed that mindfulness and self-compassion significantly influenced students' grit. These findings suggest that students' ability to recognize their experiences without judgment and treat themselves well fully contributes to the formation of perseverance in achieving goals. This study recommends developing a mindfulness- and self-compassion-based guidance and counseling service program, integrated with Islamic values ​​, to improve students' grit.